Meine Name ist Jagdish Bhatt . My Name is Jagdish Bhatt - Heinzel, Gunter (Heinzel, Gunter, 2006)
Verzio FF submission Jagdish Bhatt is a new Delhi slum dweller who, with brains, charm, and wit, repeatedly manages to overcome the narrow limits of his slum to work in Europe so he can feed his family of ten. He is a wanderer between worlds, a representative of the "globalization from below," where borders between the first and third worlds have become more porous and more rigid. Jagdish takes us through Kathputli Colony (Puppet Colony), where he lives. More than 3000 families live there, most of them artists: acrobats, snake conjurers, musicians, monkey trainers, magicians. In 2007 this unique colony will be torn down for the construction of a metro station -- a life-threatening situation for Jagdish. We meet a man who straddles extremes: while his puppetry is admired by a culturally aware public in Europe, in India he is just a face in a crowd. And while he is exposed to the seduction of money and sex in Europe, in India he wages a bitter struggle to survive.